Análisis comparativo entre blog y los sitios web y su incidencia en la transmisión de información cultural, social y política de la Ciudad de Babahoyo - Rivera Romero, Orlando Israel (2020)
The increasing number of computers with internet access and the advancement of the digital world, with the increased growth of companies seeking to be part of this web contour due to the expansion of social networks that have caused websites and Blogs are an element of habitual use when transmitting cultural, social and political information. The present case study shows the results of investigating some definitions from various sources on websites and blogs and establishing a comparative analysis. The main objective of this research case is to determine the contents of websites and blogs and their impact on the transmission of cultural, social and political information of the city of Babahoyo; so that this research was also carried out to contribute in the area of social communication by clarifying questions as to what means are used most frequently, in the same way this research will contribute as knowledge for future professionals.